PERAN PEREMPUAN DALAM RESOLUSI KONFLIK REHABILITASI DAN REKONSTRUKSI PASAR RAYA PADANG - Ira Ariesta (Jurnal Ilmu Sosial Mamangan, 2014)
The active role of women in the process of conflict resolution expected on resulting policy with gender perspective and accelerate the process of peace. In reality, women have limited participation in the conflict resolution process, so it will result the bias gender policy and not in favour of women interest. Matrilineal cultural system is not asure that women have more power in the eforts of peace. For example is the case of rehabilitation and reconstruction conflict at Pasar Raya Padang after September 30th, 2009 earthquake. This paper explain the role of women in the contex of Minangkabau matrilineal cultural system in the conflict resolution process at Pasar Raya Padang rehabilitation and reconstruction. This paper describe participation, the strength and weakness of women, and the meaning of matrilineal culture for the role of women in the process of conflict resolution.